1999
DOI: 10.1002/(sici)1097-4555(199912)30:12<1073::aid-jrs487>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopic study of photochromicN-[4-(4-n-alkoxybenzoyloxy)-2-hydroxybenzylidene]chloroanilines

Abstract: N -[4-(4-n-Alkoxybenzoyloxy)-2-hydroxybenzylidene]chloroanilines [nAHmCl (n = 1-8; m = 2, -ortho; m = 3, -meta; m = 4, -para)] were newly synthesized. Some of them exhibited a photochromic color state on ultraviolet irradiation. In 1AH2Cl, the fresh solid species as prepared by crystallization from ethanol solution was highly photochromic, more so than any of the other compounds studied. The solid species derived from the melt was hardly photochromic but was thermochromic. The species became photochromic on an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2005
2005

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Potashnik and Ottolenghi have suggested that the molecular rearrangement is the cis-trans isomerization due to rotation about the bond including the benzene ring [4]. It has also been suggested by means of Raman spectra that the photochromic behavior can be explained by a change in the twist angle of the aniline ring to the salicylidene part of the molecule [16]. Recently, it has been shown by use of X-ray diffraction analysis that an interconversion between the enol and trans-keto form is responsible for the color change [17].…”
Section: Liquid Crystalline Properties and Photochromism 129mentioning
confidence: 99%
“…Potashnik and Ottolenghi have suggested that the molecular rearrangement is the cis-trans isomerization due to rotation about the bond including the benzene ring [4]. It has also been suggested by means of Raman spectra that the photochromic behavior can be explained by a change in the twist angle of the aniline ring to the salicylidene part of the molecule [16]. Recently, it has been shown by use of X-ray diffraction analysis that an interconversion between the enol and trans-keto form is responsible for the color change [17].…”
Section: Liquid Crystalline Properties and Photochromism 129mentioning
confidence: 99%